3517 Cancer-Related Pain is a Predictor of In-hospital Opioid Overdose among Postoperative patients. (27th March 2019) - Onyeakusi, Nnaemeka E; Mukhtar, Fahad; Oshunbade, Adebamike; Gbadamosi, Semiu; Adejumo, Adeyinka; Owoh, Jude C.
Abstract : OBJECTIVES/SPECIFIC AIMS: Our study's primary aim is to determine if there is an association between cancer-related pain among patients who underwent major elective procedures and postoperative opioid overdose. In addition, the relationship between cancer-related pain in this population and inpatient mortality, total hospital charge and length of stay was assessed. METHODS/STUDY POPULATION: Our study sample consisted of adults 18 years and older who had at least one of eight elective procedures. Data was obtained from the National Inpatient Sample (NIS). Variables were identified using ICD-9 codes. Our primary predictor was cancer-related pain while our primary outcome was opioid overdose. Secondary outcomes were inpatient mortality, length of stay and total charge. Propensity-matched regression models were employed in assessing the association between cancer-related pain and outcomes of interest. RESULTS/ANTICIPATED RESULTS: Among 4, 085, 355 selected patients, 0.8% (n = 2, 665) had cancer-related pain while 99.92% (n = 4, 082, 690) had no diagnosis of cancer-related pain. All subjects with cancer-related pain (n = 2, 665) were successfully matched to subjects with no diagnosis of cancer-related pain in a 1:5 ratio yielding 13, 325 controls. Patients with cancer-related pain had significantly higher odds of opioid overdose (aOR 4.82 [95% CI [2.68-8.67]; p-value <0.0001) and inpatient mortality (aOR 1.39[1.11-1.74]; p-value 0.0043). Patients with cancer-related pain were also likely to stay significantly longer in the hospital (12.76 days vs. 7.88 days) with significantly higher total hospital charges ($140, 220 vs. $88, 316). DISCUSSION/SIGNIFICANCE OF IMPACT: Pain is a common complication of cancer pathogenesis, diagnosis or treatment. Though a rare outcome, opioid overdose could lead to undesirable outcomes. Cancer patients undergo invasive diagnostic and therapeutic procedures as part of their cancer management or for conditions not related to their primary cancer diagnosis. Safety measures including alternatives to opioids are recommended to prevent the poor clinical outcomes and higher healthcare utilization indices associated with opioid overdose in this population.